Risk factors of strabismus surgery among pediatric cerebral palsy population with strabismus in Taiwan: A population-based cohort study. Issue 12 (1st October 2020) - Lai, Wei-Yu; Kuo, Tsu-Jen; Lee, Ching-Chih; Yin, Chun-Hao
Abstract : Background: To identify the risk factors of strabismus surgery among Taiwanese children with severe cerebral palsy (CP) and strabismus. Methods: This retrospective nationwide population-based cohort study examined a cohort of newly diagnosed pediatric CP patients (age ≤ 10 y) between 1997 and 2013 with strabismus. The primary endpoint was strabismus surgery. A stepwise logistic regression was applied to determine the demographic factors, ophthalmic conditions, and comorbidities associated with strabismus surgery. Results: Out of 808 patients, 115 had received strabismus surgery. The significant factors correlated to strabismus surgery in pediatric patients with severe CP and strabismus were CP diagnosis age < 4 years, residency in a suburban/rural area, low birth weight, and strabismic amblyopia. Conclusion: In CP children with strabismus who have risk factors of younger CP diagnosis age (age < 4 y), residency in a suburban/rural area, a low birthweight, and the presence of strabismic amblyopia, strabismus surgery should be considered.